Piezoelectric Ceramic Resonators - Erhart, Jiří; Půlpán, Petr; Pustka, Martin (Topics in Mining, Metallurgy and Materials Engineering,, 2017)
This book helps the reader to understand the specific properties of piezoelectric ceramic resonators. It provides their theoretical description by immitance and equivalent circuit method. The nummerical modelling described is accompanied by examples of properties measured experimentally. Piezoelectric ceramic transformers are also covered, followed by a series of solved and unsolved problems prepared specially for students. .